Factors related to preventive COVID-19 infection behaviors among people with mental illness (2020)
Background/Purpose: Because of the spread of novel coronavirus disease 2019 (COVID-2019), preventive COVID-19 infection behaviors become important for individuals, especially those who are vulnerable. The present study proposes a model to explain the preventive COVID-19 infection behaviors among people with mental illness in Taiwan. Methods: A cross-sectional design was carried out and 414 patients with mental illness (230 males [55.6%]; mean age Z 46.32 [SD Z 10.86]) agreed to participate in the study. All the participants completed the Preventive COVID-19 Infection Behaviors Scale, Self-Stigma ScaleShort, Believing COVID-19 Information Scale, Fear of COVID-19 Scale, and Depression Anxiety Stress Scale-21. Regression models and structural equation modeling (SEM) were applied to examine the factors associated with preventive COVID-19 infection behaviors. Results: Both regression models and SEM showed that trust in COVID-19 information sources (standardized coefficient [b] Z 0.211 in regression; b Z 0.194 in SEM) and fear of COVID-19 (b Z 0.128 in regression; b Z 0.223 in SEM) significantly explained preventive behaviors among individuals with mental illness. The SEM further showed that fear of COVID-19 was significantly explained by trust in COVID-19 information sources (b Z 0.220) and self-stigma (b Z 0.454).